2020
DOI: 10.1155/2020/8398063
|View full text |Cite
|
Sign up to set email alerts
|

Differential Measurement for Cavity Ring-Down Spectroscopy with Dynamic Allan Variance

Abstract: The method of dynamic Allan variance (DAVAR) is used to analyze the time-varying characteristics of a nonstationary signal and is thus incorporated to evaluate the random error in the cavity ring-down spectroscopy (CRDS) experiments. With the numerical simulation of the influence of instabilities of sudden, slow, or periodic changes on the measurement accuracy in the ring-down process, DAVAR is proved to be an effective way to evaluate random error characteristics in an interfering environment. In order to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Huang found that laser shut-off modulation using current modulation deteriorates its thermal stability, limiting detection frequency [5] . Mo proposed a current local modulation technique, which, by adding localized periodic modulation components on top of DC modulation, improved gas detection frequency [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Huang found that laser shut-off modulation using current modulation deteriorates its thermal stability, limiting detection frequency [5] . Mo proposed a current local modulation technique, which, by adding localized periodic modulation components on top of DC modulation, improved gas detection frequency [6] .…”
Section: Introductionmentioning
confidence: 99%